2021
DOI: 10.1007/s40629-021-00163-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted micronutrition via holo-BLG based on the farm effect in house dust mite allergic rhinoconjunctivitis patients – first evaluation in a standardized allergen exposure chamber

Abstract: Purpose Evaluation of a lozenge for targeted micronutrition (holo-BLG), a new invention based on the farm effect, in house dust mite (HDM) allergic rhinoconjunctivitis (ARC) patients in a standardized allergen exposure chamber (AEC). Methods Eligible HDM allergic patients were exposed to HDM raw material in an AEC for 120 min before (V1) and after (V3) 3 months of holo-BLG supplementation. Nasal, conjunctival, bronchial and other symptoms were rated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 38 publications
6
48
0
Order By: Relevance
“…Furthermore, there are patients who are simply not suitable or motivated to receive an AIT course of 3 years. A unique opportunity for allergic patients presents itself, based on correcting micronutritional deficiencies which provide an antigen-unspecific immune-regulatory effect resulting in resilience to immune activation-"immune resilience"-and protection against allergic sensitization and symptoms [2,3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are patients who are simply not suitable or motivated to receive an AIT course of 3 years. A unique opportunity for allergic patients presents itself, based on correcting micronutritional deficiencies which provide an antigen-unspecific immune-regulatory effect resulting in resilience to immune activation-"immune resilience"-and protection against allergic sensitization and symptoms [2,3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with holo-BLG achieved a significant improvement of 60% (p = 0.0034) in the primary endpoint (total nasal symptom score) [20].…”
Section: Holo-blg-targeted Micronutrition Of Immune Cells Leads To Immune Resiliencementioning
confidence: 95%
“…In summary, the available study results [19,20] and the associated immunological effects [11] indicate that supplementation with holo-BLG can lead to immune resilience in patients with allergic rhinitis, whereby this phenomenon is not allergen-specific. The preclinical data could now be supported accordingly by early clinical data.…”
Section: Holo-blg-targeted Micronutrition Of Immune Cells Leads To Immune Resiliencementioning
confidence: 99%
“…When BLG shuttles ligands into immune cells, it causes immuneresilience, while uptake without ligands evokes a Th2-response in vitro, resulting in allergy in murine models. [17][18][19][20][21][22] Moreover, symptom reduction could be achieved by consumption of loaded BLG in house dust-mite allergic 23 and birch pollen allergic patients. 24 Apart from this being an important immunological observation, following the One Health concept, we must scrutinize its systematic impact for humans and animals.…”
mentioning
confidence: 99%
“…It was shown that the loading of BLG with vitamins and iron complexes is decisive: When BLG shuttles ligands into immune cells, it causes immune‐resilience, while uptake without ligands evokes a Th2‐response in vitro , resulting in allergy in murine models. 17 , 18 , 19 , 20 , 21 , 22 Moreover, symptom reduction could be achieved by consumption of loaded BLG in house dust‐mite allergic 23 and birch pollen allergic patients. 24…”
mentioning
confidence: 99%